Penyuluhan Pemanfaatan Lahan Kosong di Desa Rawabelut, Kecamatan Sukaresmi, Kabupaten Cianjur - Nada Radilla; Agung Sandi Budiman; Idung Risdiyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
One of the problems faced by the people of Rawabelut Village in utilizing vacant land or yards is the lack of good knowledge and skills. The existence of counseling and training activities is one of the efforts that must be done. This activity aims to increase the knowledge and skills of the people of Rawabelut Village regarding the techniques of utilizing vacant land properly, as well as increasing knowledge about the kinds of innovations that can be carried out for utilizing vacant land. The method used is counseling with two-way discussions with the community held at Rawabelut Village Hall. The implementation of the program to use the house yard is running smoothly and the community has the awareness and willingness to plant vegetable and fruit plants in their respective plots. Counseling activities carried out by describing material about verticulture methods. The people of Rawa Belut Village welcome and participate actively in every activity carried out. Keywords: Counseling, Rawabelut village, vegetable and fruit plants, verticulture, yard